IMPLEMENTASI PROGRAM URBAN FARMING DI KELURAHAN BAMBANKEREP KECAMATAN NGALIYAN KOTA SEMARANG - Dea Elvaretta, Inez; Marom, Aufarul; Nurcahyanto, Herbasuki (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2024)
Urban Farming is one of the community empowerment initiatives in agriculture implemented by the Semarang City Government. The program aims to reduce poverty, improve community skills, and serve as a learning and human resource development tool in the agricultural sector. The Urban Farming program is also a strategy to improve food security amidst limited land and increasing food demand due to rapid population growth. By utilizing small lands such as home yards, this program is expected to make a significant contribution. This study is a descriptive qualitative research that aims to describe the implementation of Urban Farming program in Bambankerep Village, Ngaliyan Sub-district, Semarang City. Based on the research results, the implementation of the Urban Farming program in Bambankerep Village has not been well implemented. The implementation of the Urban Farming program has not yet reached the aspect of compatibility between implementers and users. In terms of achieving results, it has not been achieved optimally and the community cannot feel the results optimally due to several obstacles faced related to human resources, facilities and infrastructure and other problems. Recommendations from the results of this study are the need for the government to pay more attention and embrace the Women Farmers Group (KWT) in an effort to implement Urban Farming, especially by improving communication between KWT members and increasing the awareness and enthusiasm of members of the Women Farmers Group (KWT), the need to fulfill infrastructure needs, and the need to develop SOPs that specifically regulate the implementation of the Urban Farming program.